The embodiment controversy: On the policy implications of vintage capital models - SAMANIEGO, Roberto M. (Institutional Knowledge at Singapore Management University, 2022)
We explore the long-run impact of policy on the level of economic activity through changes in the vintage distribution of capital, in a model where different vintages coexist in production. Because firms can choose the vintage of capital in which they invest, investment subsidies do not affect the vintage structure of capital. In contrast, vintage-specific taxes or subsidies that target the newest vintages of capital can significantly affect output and welfare in the long run, mainly downward. Transition dynamics are rapid, so that steady-state comparisons give an accurate picture of the welfare impact of vintage tax wedges.